PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN KEPEMILIKAN SAHAM PUBLIK TERHADAP PENGUNGKAPAN CSR - indraswari, gusti ayu dyah; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2014)
Corporate Social Responsibility (CSR) is a factor that affect the development and  withstand of company. This CSR research purpose is to verify profitability effect,company, size and public ownership share in disclosure of csr. Research population is 11 companies of food and drink that registered in BEI from 2010-2012 with purposive sampling technique, so that total sample within 3 years is 33 sample. Data analysed by using descriptive statistic analyse technique, classic assumption test and hypotheses test are using doubled regression. The results are profitability and company size have positive effect but public ownership share have negative effect in disclosure of CSR.
Keywords: Profitability, size, public ownership, CSR